(untitled) (REMUNOM, 2025)
Human resources management is a dynamic science area requiring periodic assessments to summarize what is known about the subject. Regular reviews bring a better understanding of organizations’ operating logic, evolution, and data for developing more appropriate HR management practices. Thus, this study proposed a conceptual definition of human resources management based on scientific literature. The conceptual bibliographic method was used in its four stages to generate its findings: 1) problem formulation and response pattern, 2) data collection in the Google Scholar scientific base, 3) data organization based on semantic analysis, and 4 ) presentation of the answers sought. The results showed nine predominant terms of equivalence: process, approach, strategy, set, system, activity, contracting, progress, and art, and seventeen attributes, grouped into six semantic axes characterizing human resources management: management, employees, development, strategic, goals, and organization. The conclusion presents a conceptual proposal that human resources management can be defined as a strategic management process for developing employees to achieve personal and organizational goals. The study’s contribution to science is the proposition of a conceptual definition with adequate boundaries of the scope of the phenomenon of human resources management beyond reductionist and simplistic approaches, which favors organizational practices.